Restoration of soils contaminated with radionuclides by phytoredomediation method - Udalov, I.V.; Peresadko, V.A.; Polevich, O.V.; Kononenko, A.V. (Вопросы атомной науки и техники, 2020)
The possibility of soil restoration by means of phytotechnology and artificial geochemical barriers (GB) from contamination by radionuclides (RN) and toxic elements (TE) is methodologically substantiated. For this purpose, a number of artificial GBs were created at a special landfill within the framework of a model experiment. The process of formation and development of barriers, their parameters are investigated. Agrophytocenosis cultures were selected for optimal phytostabilization of soil conditions. The study of phytoextraction of TE and RN by agrophytocenosis cultures during one complete vegetation period was performed. Some selectivity of the investigated plants for extraction of different TEs and RNs from soils and material of barriers was revealed. Методологічно обґрунтована можливість відновлення стану ґрунтів за допомогою фітотехнологій та штучних геохімічних бар'єрів (ГБ) від забруднення радіонуклідами (РН) і токсичними елементами (ТЕ). Для цього створено ряд штучних ГБ на спеціальному полігоні в рамках модельного експерименту. Досліджено процес формування та розвитку бар'єрів, визначені їх параметри. Вибрано культури агрофітоценозів для оптимальних варіантів фітостабілізації стану ґрунтів. Виконано дослідження фітовилучення токсичих елементів (ТЕ) і РН культурами агрофітоценозів протягом одного повного вегетаційного періоду. Виявлена певна селективність досліджуваних рослин щодо вилучення різних ТЕ і РН з ґрунтів і матеріалу бар'єрів. Методологически обоснована возможность восстановления состояния почв с помощью фитотехнологий и искусственных геохимических барьеров (ГБ) от загрязнения радионуклидами (РН) и токсичными элементами (ТЭ). Для этого создан ряд искусственных ГБ на специальном полигоне в рамках модельного эксперимента. Исследован процесс формирования и развития барьеров, определены их параметры. Выбраны культуры агрофитоценозов для оптимальных вариантов фитостабилизации состояния почв. Выполнены исследования фитоизвлечения ТЭ и РН культурами агрофитоценозов в течение одного полного вегетационного периода. Выявлена определенная селективность исследуемых растений по изъятию различных ТЭ и РН из почвы и материала барьеров.